Tinjauan Ontologi, Epistemologi, dan Aksiologi terhadap Guru Profesional - Nurhadi Kastamin; Saeful Anwar; Nur Afif (Jurnal Dirosah Islamiyah, 2021)
Professional teachers according to the ontology review are teachers who are required to have academic qualifications, competencies, educator certificates, physically and mentally healthy, and have the ability to realize national education goals. As for the epistemological review, to realize a professional teacher there are four stages that must be taken, namely: 1). Provision of university-based teachers, 2). Induction for novice teachers based on school, 3). Professionalization of teachers based on institutional initiatives, and 4). Teacher professionalization on an individual basis or becoming a civil teacher. While axiologically, professional teachers function to elevate dignity, act as learning agents to improve the quality of national education, aim to implement the national education system and realize national education goals. For this dedication, teachers as professional workers are entitled to receive, such as salary or income, respect, appreciation, protection, social welfare and so on. The purpose of this research is to find out in depth the professionalism of teachers by using a theoretical approach to the philosophy of science, namely in terms of ontology, epistemology, and axiology. This research is library research, namely the data needed to complete the research obtained from the library in the form of books, encyclopedias, dictionaries, journals, documents, magazines and so on..